Perasaan kompeten sebagai orang tua: Pengalaman ibu dari remaja pelaku kekerasan seksual - Mafaza Mafaza; Nila Anggreiny; Septi Mayang Sarry; Agung Rachmad (Jurnal Ilmiah Psikologi Terapan, 2022)
Juveniles are also involved in behaviors that violate the law, such as in cases of sexual violence. This study aims to describe the experiences of mothers whose children are perpetrators of sexual violence. The study used a qualitative phenomenological method. Five mothers of a sexual offender charged by the juvenile court participated in this study. They were interviewed about their parenting experiences using in-depth interviews. The data were analyzed using interpretative phenomenological analysis (IPA). Thirteen subordinate themes were found and grouped into three superordinate themes, including (1) feeling like a mother, (2) role of mothers, (3) maternal sense of competence. The mothers of juvenile sexual offenders perceived that they had failed as parents and that parenting competence was lacking. They considered peer influence and uninvolved partners in parenting practice as the source of difficulties in managing their child’s problematic behavior.